COMPENSATION METHOD FOR FUNCTIONAL SIMULATION OF SUBMICRON VLSI CIRCUITS - Новосядлий, Степан Петрович; Бережанський, Володимир Михайлович; Бойко, Сергій Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Designing complex electronic devices it is important to know how the signal is converted as it passes from input to output of device or system. There are two cases of such modeling, in the first case VLSI circuit is modeled based on physical approach by method of circuit simulation, in the second case – on the basis of information approach by functional modeling. The goal of the compensation method is elimination of frequency dependent phase shift by using correcting RC-circuit. It transforms inertial circuit elements in non-inertial, non-linear in linear. This method is developed with aim to increase performance of signal CAD. For proper operation of CAD it is necessary to develop a library of active elements with a certain cutoff frequency and power with corresponding RC-correlators.